Five-year survival after sigmoid resection and low vascular ligation versus left hemicolectomy and high ligation for stage I–III sigmoid carcinoma: a retrospective study - Vitkauskas, Vytautas; Samalavičius, Narimantas Evaldas; Vitkauskienė, Marija (Acta medica Lituanica, 2014)
Background. There is still a discussion whether or not high ligation of the inferior mesenteric artery and vein during surgery for sigmoid cancer has survival benefit compared to low ligation. Both operations are used today. The aim of our study was to evaluate retrospectively 5-year survival after low ligation in comparison with high ligation for stage I–III sigmoid cancer. Materials and methods. We reviewed 127 patients who were operated on for stage I–III sigmoid cancer during the period of 5 years (1 January 2003 – 31 December 2007) at the Oncology Institute of Vilnius University. Left hemicolectomy was performed in 20 cases (Group 1), whereas sigmoid resection was performed in 107 cases (Group  2). In Group  1 there were 10 men and 10 women, mean age was 66.4 (std. dev. 7.816, range 50–78). In Group 2 there were 46 men and 61 women, mean age was 66.71 (std. dev. 9.964, range 40–82). Results. Mean hospital stay was 15.8  days (std.  dev.  4.895, min.  10, max. 30) in Group 1 and 17.47 days (std. dev. 4.995, min. 7, max. 37) in Group 2 (p > 0.005). There were 2 postoperative complications in Group 1 (10%) and 27 in Group 2 (25.2%) (p > 0.005). 5-year survival in Group 1 was 70%, in Group 2 it was 72.9% (p > 0.005). Conclusions. In our study there was no significant difference in operating time and other variables between the groups, but higher postoperative complication rate and a longer hospital stay was observed after sigmoid resection with low ligation in comparison with left hemicolectomy with high ligation. However, five-year survival rate was not different between the groups. In conclusion, our findings conclude that both techniques give adequate oncological results in cases of sigmoid cancer.
Keywords: sigmoid cancer; high-ligation; low-ligation; sigmoid resection; left hemicolectomy